Visibility widgets for unveiling occluded data in 3D terrain visualization. (October 2017) - Röhlig, Martin; Luboschik, Martin; Schumann, Heidrun
Abstract: In 3D visualization of terrain, occlusion has detrimental impact on discovering, accessing, and spatially relating embedded data. This can lead to significant loss of information. To address this issue, we introduce visibility widgets: compact auxiliary views that visualize occluded data, their locations, and related properties, and thus support users in revealing hidden information. The widgets comprise different occlusion management strategies for detecting and analyzing invisible data inside as well as outside of the field of view. In addition, each widget is designed complementary and transient to facilitate interactive exploration and navigation while not monopolizing the user's attention. We demonstrate the application of visibility widgets focusing the visual exploration of weather data in 3D terrain.